THE INFLUENCE OF COLLECTION USABILITY LEVEL ON COLLECTION UTILIZATION IN THE LIBRARY AND PUBLISHING - Syafrita, Nella; Rahmah, Elva (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Libraries play a crucial role as centers of information resources, supporting academic activities within higher education institutions. However, the effectiveness of library collection utilization largely depends on the level of collection usability. This study aims to describe the level of collection usability, the level of collection utilization, and analyze the influence of collection usability on collection utilization at the Library and Publishing Unit of Padang State University. This research employed a quantitative approach using a descriptive-correlational design. A total of 100 respondents were selected through simple random sampling from the population of library visitors between August and October 2024. Data were collected through a questionnaire and analyzed using normality tests, Pearson correlation, simple linear regression, and the coefficient of determination. The results indicate that the level of collection usability is categorized as good, with an average score of 3.48, while the level of collection utilization is also classified as good, with an average score of 3.795. Correlation analysis reveals a strong positive and significant relationship between collection usability and collection utilization, with a Pearson correlation coefficient of 0.837 (p < 0.001). The regression analysis shows that the level of collection usability contributes 70.1% to collection utilization, while the remaining 29.9% is influenced by other unexamined variables. This study concludes that the higher the level of collection usability, the more optimal the utilization of library collections by users. The findings highlight the importance of continuous collection updates, routine surveys of users' information needs, and enhanced access to digital resources. These strategies are essential to maximize collection utilization in support of learning, research, and knowledge development within higher education settings.